Criminalization of the Private Sector (Bribery in the Private Sector) in Overcoming Gratification Against Doctors in Medical Services - David Raja Pangihutan; Madiasa Ablisar; Marlina Marlina; Syarifah Lisa Andriati (JUSTICES: Journal of Law, 2026)
Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia confirms that everyone has the right to obtain health services. Then in Chapter XIV Article 33 paragraph (1) emphasizes that the economy is structured as a joint effort based on the principle of kinship. Paragraph (2) emphasizes that the earth, water and natural resources contained therein are controlled by the state and used as much as possible for the prosperity of the people. Furthermore, Article 34 paragraph (1) confirms that the poor and neglected children are cared for by the State, paragraph (2) confirms that the State develops a social security system for all people and empowers the weak and underprivileged with human dignity, paragraph (3) states that the state is responsible responsible for providing adequate health services and public facilities. In the Era of Reform and the challenges of globalization, people's demands for the availability of health services that are fast, precise, sophisticated, high quality and enjoyable and at affordable costs can truly be felt by the community. Health is a human right, where everyone has the right to a decent life, which includes good health.